Islam in Kosovo And the impact of the teachings of Prophet Muhammad SAW in the lives of local Muslim Women - Bisa Ismaili Ahmeti (Seerat Studies, 2023)
Religion plays an important role in the lives of women of Western Balkan in general and of women in Kosovo in particular. Muslims in the Peninsula are native non-immigrant nations who have embraced Islam seven centuries ago or even earlier. At the crossroads between Occident and Orient, women of Balkans have gone through difficult experiences. The religious lives have gone through various institutional transformations. And today`s institutional landscape is the result of century long processes of historical and societal shifts. This paper is an attempt to portray the Islamic institutional organization in general and how it has impacted women believers, the teachings of Islam and its tremendous spiritual impact in their lives. Key words: Islam, Religion, Women, Seerah.